2022
DOI: 10.1101/2022.05.10.491399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular Vesicle exchange is favored by cell proximity

Abstract: Extracellular vesicles (EVs) are biological nanovectors that retain information of the cell of origin and convey signals to recipient cells. Therefore, EVs are ideal platforms for the development of diagnostic tools and of bio-inspired drug delivery technologies. However, the dynamics of EV distribution in physiological conditions are still underexplored. Using an elegant series of experiments, including quantitative assays to define EV transfer and five dimension live cell imaging, we observe the release and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…reported an interesting observation in their preprint that cancer cells with EV labels cocultured in 2D monolayer transferred EVs only to the proximal cells, mostly within. 38 Culture with agitation did not increase EV transfer in distant orientation. Their observation indicates that EV transfer is limited even in 2D culture.…”
Section: Factors Affecting Cellular Communication Via Evs ...mentioning
confidence: 90%
See 1 more Smart Citation
“…reported an interesting observation in their preprint that cancer cells with EV labels cocultured in 2D monolayer transferred EVs only to the proximal cells, mostly within. 38 Culture with agitation did not increase EV transfer in distant orientation. Their observation indicates that EV transfer is limited even in 2D culture.…”
Section: Factors Affecting Cellular Communication Via Evs ...mentioning
confidence: 90%
“…which will also limit the distance of EV dissemination.Recently, Colombo et al reported an interesting observation in their preprint that cancer cells with EV labels cocultured in 2D monolayer transferred EVs only to the proximal cells, mostly within 38. Culture with agitation did not increase EV transfer in distant orientation.…”
mentioning
confidence: 95%
“…The increase in miR-145 was found not only in VICs harvested from MVP-affected valves but also in their associated sEV. As sEV can be taken up by neighboring cells for local cell-to-cell communication [28], the content of the sEV produced by myofibroblastic VICs can promote phenotypic transition and activation of neighboring cells and potentially exacerbate the extent of valvular pathology as activated myofibroblastic VICs contributes to the remodeling of the extracellular matrix. This important finding resonates with other recent investigations that demonstrate the importance of local (paracrine) sEV-mediated signaling in cardiac fibrosis [29] or cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…As sEV can be taken up by neighboring cells for local cell-to-cell communication [28], the content of the sEV produced by myofibroblastic VICs can promote phenotypic transition and activation of neighboring cells and potentially exacerbate the extent of valvular pathology as activated myofibroblastic VICs contributes to the remodeling of the extracellular matrix. This important finding resonates with other recent investigations that demonstrate the importance of local (paracrine) sEV-mediated signaling in cardiac fibrosis [29] or cancer [28]. sEV ncRNA content may also serve as biomarkers for disease progression; however, as our previous work in plasma sEV has shown, attempts to dissect signals only from the mitral valve may be difficult as overall systemic changes such as in heart failure will also contribute to the overall circulating sEV ncRNA content.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, only recipient cells that bind nEVs in high numbers can be detected and isolated for profiling studies ( 15 , 20 ). Remote EV-cell communications are much harder to identify as the amount of nEVs exponentially decreases with distance from EV donor cells ( 21 ). Therefore, defining the impact of nEVs on the full repertoire of local and distant recipient cells is still an unmet challenge that requires the application of paradigm-shifting technologies ( 22 ).…”
Section: Introductionmentioning
confidence: 99%